PENGARUH FUNGSI-FUNGSI MANAJEMEN TERHADAP KINERJA APARATUR SIPIL NEGARA PADA KANTOR KECAMATAN MOLAWE KABUPATEN KONAWE UTARA - sappodin sappodin; Sudirman Zaid; Sinarwaty Sinarwaty; Nursaban Rommy; Hartini Hartini; Rachmad Rialdy Hasan (Pascasarjana Universitas Halu Oleo, 2020)
This study aimed to determine the Influence of planning, organizing, actuating and controlling toward the performance of the State Civil Apparatus at the Molawe District Office, Konawe Utara Regency simultaneously and partially. The sample in this study as many 35 people Apparatus State Civil who worked at the Molawe District Office, Konawe Utara Regency. Analysis tool used is quantitative analysis using Multiple Linear Regression Analysis.The results showed that the simultaneous functions of planning, organizing, actuating and controlling had significant effect on the performance of the State Civil Apparatus at the Molawe District Office, Konawe Utara Regency. And partial functions of planning, organizing and actuating had positif significant effect on the performance of the State Civil Apparatus at the Molawe District Office, Konawe Utara Regency, so that the hypothesis can be accepted.